Comparative perspectives on past colonisation, maritime interaction and cultural integration (Sheffield, UK ; Bristol, CT)
xiii, 289 sayfa
Keywords: “This volume explores processes of colonisation and cultural integration from the end of the last Ice Age to the present from a cross-cultural and interdisciplinary perspective. All kinds of human mobility, short-distance as well as long-distance movements, short-term and long-term interactions are potential triggers for change and also cultural integration. The colonisation of an area most clearly brings into focus what kind of social fabric encompassed the actual historical processes. Recent perspectives on the social and cultural embeddedness of exchange, and how objects facilitate constructions of identities and political legitimacy, serve to frame and explicate the role of material culture in such processes. The contributions to this volume shed light on various social aspects of movement, migration and colonisation among hunter-gatherers and Neolithic groups as well as in chiefdoms and state societies. Geographically, an area spanning from the Mediterranean to Central Europe and the North Sea Region, Greenland and Siberia is covered. Three social and historical processes--the social aspects of colonisation, cultural integration and maritime interaction--are particularly discussed as interrelated phenomena.“ --